Locally aggressive recurrent sebaceous carcinoma of the scalp with post-auricular ‘kissing ulcer’: an infrequent skin appendageal neoplasm at unusual location - Jangra, Mahesh; Saini, Parampreet Singh; Shetty, Harshavardhan; Tripathy, Satyaswarup (International Journal of Research in Medical Sciences, 2026)
Sebaceous carcinoma is an infrequent malignancy that arises from skin appendageal system. It is usually common in elderly age with slightly female preponderance. Asian population have higher incidence of this malignancy. Most commonly it occurs in orbital region (75%) and rarely this tumour presents in extraocular regions like scalp, face, genitalia and extremities. This tumour can be locally aggressive, has more chances of recurrence and can spread to lymph nodes, skull bones, dura, brain and viscera. Usually there are no etiological factors implicated, but some cases may have association with Muir Torre syndrome. Definite diagnosis can be confirmed on histopathology. Accurate diagnosis and thorough management remain important against this aggressive dermatological malignancy. Here, we are presenting a case of a man in his mid 60s with recurrent sebaceous carcinoma arising from the scalp, with involvement of right post auricular area. He was managed with wide local excision and scalp rotation advancement flap. Patient did not show any evidence of local recurrence after a follow up period of 3 years. Adjuvant radiotherapy may be considered to improve the outcome for recurrent tumours. These patients should be closely followed for assessment of distant metastasis and recurrence.